2020
DOI: 10.1007/s11676-020-01238-z
|View full text |Cite
|
Sign up to set email alerts
|

Collembola communities and soil conditions in forest plantations established in an intensively managed agricultural area

Abstract: The challenges of a changing climate have directed greater attention to afforestation, but the effects of afforestation on soil fertility and soil biota have not been fully clarified. To explore changes in the soil conditions in two 20-year-old forest plantations established in formerly intensively fertilized plots of agricultural land, we focused on the current developmental state of the sites that received the most fertilizer and evaluated soil properties and Collembola (springtails) communities. Sessile oak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 114 publications
1
33
0
1
Order By: Relevance
“…Shannon index was a sensitive parameter for Collembola diversity, and agreed withAndres and Mateos (2006), who found it a suitable indicator to assess soil cover treatments in post-mining sites Harta et al (2021). found that the diversity of Collembola increased with soil organic matter (SOM) content, which agrees with the current findings, andMudrak et al (2012) found that the species composition of the Collembola community was altered by increasing litter quality.The highest density for Collembola was found in the tailings and subsoil treatments.…”
supporting
confidence: 88%
“…Shannon index was a sensitive parameter for Collembola diversity, and agreed withAndres and Mateos (2006), who found it a suitable indicator to assess soil cover treatments in post-mining sites Harta et al (2021). found that the diversity of Collembola increased with soil organic matter (SOM) content, which agrees with the current findings, andMudrak et al (2012) found that the species composition of the Collembola community was altered by increasing litter quality.The highest density for Collembola was found in the tailings and subsoil treatments.…”
supporting
confidence: 88%
“…Rubber tree residues (trunk, leaves, stump and fine branch) and the legume on the ground constitute large quantities of accumulated OM that can harbor a greater abundance of springtails [ 51 ]. In addition, this high OM presence may increase the resource heterogeneity necessary for increased springtail abundance [ 52 ]. In the R0L0 practice, the absence of OM leads to a degradation of the habitat quality, which prevents many springtails to colonize this habitat [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the agricultural soil is frequently subjected to continuous disturbances like tillage operations and harrowing which leads to the drying of the uppermost layers, as well as remove the litters from the soil surfaces, making the ecological niche quite unfavourable for the soil fauna [23,24]. Adoption of chemo-centric agriculture as well as injudicious application of synthetic pesticides in tea plantations for biotic stress management also alters the chemical properties of the soil and exerts lethal impact on collembolan population [25,26].…”
Section: Discussionmentioning
confidence: 99%